Effect of statins on bone mineral density and bone histomorphometry in rodents. - Maritz, F; Conradie, M; Hulley, P; Gopal, R; Hough, S (2001)
Statins have been postulated to affect bone metabolism. We investigated the effects of different doses of simvastatin (1, 5, 10, and 20 mg. kg(-1). d(-1)), atorvastatin (2.5 mg. kg(-1). d(-1)), and pravastatin (10 mg. kg(-1). d(-1)) administered orally for 12 weeks to intact female Sprague-Dawley rats and the effect of 20 mg. kg(-1). d(-1) simvastatin in sham-operated and ovariectomized rats on femoral bone mineral density (BMD) and quantitative bone histomorphometry (QBH) and compared them with controls. BMD was decreased by 1 mg. kg(-1). d(-1) simvastatin (P=0.042), atorvastatin (P=0.0002), and pravastatin (P=0.002). The effect on QBH parameters differed with different doses of simvastatin (ANOVA, P=0.00012). QBH parameters of both bone formation and resorption were equivalently and markedly increased by 20 mg. kg(-1). d(-1) simvastatin in 2 separate groups of intact rats and were reflected by a relatively unchanged BMD. At lower doses, 1 mg. kg(-1). d(-1) simvastatin decreased bone formation while increasing bone resorption, as reflected by a marked decrease in BMD. Ovariectomized animals receiving 20 mg. kg(-1). d(-1) simvastatin showed no change in BMD relative to the untreated, ovariectomized controls; their increase in bone formation was smaller than in sham-operated rats receiving simvastatin, and there was no change in bone resorption. Dose-response curves of simvastatin for bone formation and resorption differed. These studies indicate that (1) statins decrease BMD in rodents, (2) high-dose simvastatin increases bone formation and resorption, (3) low-dose simvastatin decreases bone formation and increases bone resorption, (4) the effects of simvastatin on QBH differ at different dosages, (5) the effects of simvastatin seen in intact rats are not observed in ovariectomized rats, and (6) simvastatin is unable to prevent bone loss caused by ovariectomy.